2014
DOI: 10.4314/sajas.v43i5.24
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary fatty acid saturation on egg production at end-of-lay

Abstract: ________________________________________________________________________________ AbstractThis study was conducted to investigate the effects of dietary fatty acid saturation on production performances of laying hens at end-of-lay. Five isoenergetic (12.6 MJ AME/kg DM) and isonitrogenous (170 g CP/kg DM) diets were formulated using different lipid sources at a constant 30 g/kg inclusion level. The control diet was formulated using a blend (50 : 50) of linseed-and fish oil, while the other treatments consist of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 15 publications
1
3
0
Order By: Relevance
“…These authors reported no significant differences in hen-day egg production, egg weight, egg output, feed efficiency, and body weights at end-of-lay. Similar results were reported by Cachaldora et al [44,45] who concluded that dietary fatty acid saturation had no significant effects on the egg production performance of layer hens. In contrast, Shang et al [46] stated that body weight gain, rate of egg production, egg weight, and feed efficiency decreased linearly with an increase in dietary fatty acid unsaturation levels during the 8-week experimental period between 40 and 48 weeks of age.…”
Section: Beneficial Applications Of ω-3 and ω-6 Oils In Poultrysupporting
confidence: 90%
“…These authors reported no significant differences in hen-day egg production, egg weight, egg output, feed efficiency, and body weights at end-of-lay. Similar results were reported by Cachaldora et al [44,45] who concluded that dietary fatty acid saturation had no significant effects on the egg production performance of layer hens. In contrast, Shang et al [46] stated that body weight gain, rate of egg production, egg weight, and feed efficiency decreased linearly with an increase in dietary fatty acid unsaturation levels during the 8-week experimental period between 40 and 48 weeks of age.…”
Section: Beneficial Applications Of ω-3 and ω-6 Oils In Poultrysupporting
confidence: 90%
“…In this study, levels of n-3 and n-6 PUFA also increased in accordance with the increasing lupin meal content in the feed mixture. By contrast Buitendach et al (2013) did not find any impact of supplementing fatty acids into the feed mixture for hens on their productivity. They added to the feed mixtures linseed oil, fish oil, sunflower oil and tallow.…”
Section: Discussionmentioning
confidence: 63%
“…This is because the crude protein content in all treatments was not different (22%), although the omega-3 content was different. Fatty acid saturation was significantly influence production of laying hens at the end of production period (58-74 weeksold), on egg production performance, egg weight, egg production, feed efficiency, and body weight (Buitendach et al 2014). Egg production is influenced by linoleic fatty acid and amino acid methionine.…”
Section: Egg Productionmentioning
confidence: 99%